Pengaruh Cukai dan Pajak Rokok terhadap Penerimaan Cukai melalui Harga Eceran Perusahaan Rokok di Kabupaten Kudus - Dimas Imam Santosa; Supriyono Supriyono; Mira Meilia Marka (Universitas Muhammadiyah Magelang, 2021)
This research is motivated by excise tax which gives the biggest contribution to local government excise revenue. And excise revenue from 2017 to 2019 at the Directorate General of Customs and Excise, Kudus year after year has decreased in the achievement of excise revenues and is accompanied by excise targets. The determination of this sample used a purposive sampling method with a sample size of 162 companies with the period 2018-2019 which were registered as Offices Supervision and Customs Service Type Intermediate Excise Kudus. This study uses analysis techniques Part analysis and Sobel Test. The results of this study indicate that excise costs and cigarette taxes have a significant effect on the retail price, while excise costs, cigarette taxes, and retail prices have an effect on excise revenue. The retail selling price has a strong mediation between excise tax and excise revenue, while the retail selling price does not have a strong (low) mediation between cigarette taxes and excise revenue.